The Gut Microbiota of Pheasant Lineages Reflects Their Host Genetic Variation - Ding, Jinmei; Jiang, Ting; Zhou, Hao; Yang, Lingyu; He, Chuan; Xu, Ke; Akinyemi, Fisayo T.; Han, Chengxiao; Luo, Huaixi; Qin, Chao; Meng, He (Frontiers in Genetics, 2020)
The host gut colonized enormous microbial community, which can be influenced by diet, diseases, behavior, age, gender, hereditary effects, and environmental factors. However, the relationship between gut microbiota and host genetic variation has not yet been elucidated. In this study, we chose five pheasant lineages—Ring-necked pheasant (RN), Manchurian pheasant (MX), Phasianus versicolor (PV), Shenhong pheasant (SP), and Melanistic mutant pheasant (MM)—to investigate the gut microbial composition of pheasants and its relationship with host genetic variation. Microbial classifications revealed 29 phyla and 241 genera presented in pheasants, with the dominant phylum of Firmicutes and the genus of Lactobacillus. Statistical analyses suggest that the relative abundance of 75 genera was significantly different among the five lineages. The most abundant genus carried by the RN and MM was Streptococcus, which was significantly lower in PV (P=0.024). Conversely, Lactobacillus was the major genera in PV and MX. Moreover, the RN had the greatest microbial abundance, with a remarkably different microbial community than PV. The gut microbial diversity of PV was the lowest and diverged significantly from the RN and MX. Interestingly, the clustering of the MM and SP in the microbial dendrogram corresponded to their cluster in the host phylogeny. The host phylogenetic split of the RN, MX, and PV echoed their microbial distance. In conclusion, the congruence of host phylogeny and their gut microbial dendrograms implies that gut microbiota of pheasant lineages could reflect their host genetic variation.